A focus on the distinctions and current evidence of endometriosis in adolescents. (August 2018) - de Sanctis, Vincenzo; Matalliotakis, Michail; Soliman, Ashraf T.; Elsefdy, Heba; Di Maio, Salvatore; Fiscina, Bernadette
Abstract: Endometriosis (EM) occurring in adolescents presents distinct clinical and histologic characteristics compared to the disease in women. Because the symptoms of EM are nonspecific, often overlapping with those experienced in a range of gynecological and gastrointestinal conditions, the process of reaching a diagnosis of EM is often delayed. The diagnosis of EM is suspected depending on the history and the symptoms and signs, is corroborated by physical examination and imaging techniques, and is finally proved by histological examination of specimens collected during laparoscopy. Currently, there is insufficient evidence to make strong recommendations for management in adolescents who may have EM. This short report reviews some peculiarities of EM in adolescents and provides an update of recent knowledge of the diagnosis and treatment of EM. We hope that the present contribution may help to bring more attention to the clinical diagnosis of EM and consequently aid in decreasing diagnostic delay. Highlights: There are no large epidemiologic studies on endometriosis among adolescents. Endometriosis in adolescents may present differently from adult endometriosis. Early identification of disease may be beneficial in preventing progression and infertility. Laparoscopy with biopsy is the only way to diagnose endometriosis. Prospective observational studies are still required in the adolescent population.